When Life Got Smart: The Evolution of Behavioral Complexity Through the Ediacaran and Early Cambrian of NW Canada. (March 2014) - Carbone, Calla; Narbonne, Guy M.
Abstract : Ediacaran and early Cambrian strata in NW Canada contain abundant trace fossils that record the progressive development of complex behavior in early animal evolution. Five feeding groups can be recognized: microbial grazing, deposit-feeding, deposit-feeding/predatory, filter-feeding/predatory, and arthropod tracks and trails. The lower Blueflower Formation (ca. 560–550 Ma) contains abundant burrows that completely cover bedding surfaces with small (∼1 mm diameter) cylindrical burrows that were strictly restricted to microbial bedding surfaces and exhibited only primitive and inconsistent avoidance strategies. The upper Blueflower contains three-dimensional avoidance burrows and rare filter-feeding or possibly predatory burrows, suggesting increased behavioral responses in food gathering that marked the beginning of the agronomic revolution in substrate utilization. Cambrian strata of the Ingta Formation contain systematically meandering burrows and more diverse feeding strategies, including the onset of treptichnid probing burrows that may reflect predation. These observations imply that Ediacaran burrowers were largely characterized by crude, two-dimensional avoidance meanders that represented simple behavioral responses of individual burrowers to sensory information, and that the subsequent development of more diverse and complex feeding patterns with genetically programmed search pathways occurred during the earliest stages of the Cambrian explosion. These observations further imply that changes occurred in both the food source and substrate during the ecological transition from Proterozoic matgrounds to Phanerozoic mixgrounds.